Old facies due to cutaneous infiltrating mastocytosis. - Pedicelli, C.; Rota, C.; Angelo, C.; Paradisi, M. (European Journal of Pediatric Dermatology, 2007)
The Authors report an unusual cause of old appearance in children, presenting an infantile case of diffuse cutaneous mastocytosis. In the first months of age, this disorder runs a severe course with diffuse blistering lesions, requiring a systemic treatment, sometimes with courses of oral corticosteroids. With time diffuse cutaneous infantile mastocytosis tends to regress as well as most cases of infantile mastocytosis.